PELAKSANAAN KONSOLIDASI TANAH UNTUK PEMUKIMAN PADA DAERAH PERKOTAAN (STUDI DI PEMERINTAH KABUPATEN SIDOARJO) - Nur Hidayati; Wahyu Prawesthi (Jurnal ADIL, 2015)
ABSTRACTThe need of land to stay at residence always makes a prcblem forsociety. We often find the separated of the land that obeys fheregulation at that time depends on the need af the owner, especialty theplace to stay, They consisf of the decoration of the environment suchas roads, drainage and public facilities, There was a constiiution fromthe Head of the Land National Committee no 4 at 1gg1 about theconsolidation of land to arrange the land sysfem and environment, Theaim is to anticipate or prevent from the lack of disorder or slum area inthe location of the research at the district of Sidoardjo. tf we let it, we, have a problem in every aspect. The benefit that we got from thisresearch can be expected to contribute th'e ideas of the developmentfrom the srdes of the land and land construction especiarty about thelayr,of the land consolidation that related to the consolidation of the tandin tswns that used to stay, Beside that, the benefit of ttte resoarch is forcontextual contributisn to the institution or government institution thathandles the land field and land consolidation, The analyze of thisresearch has been got from the primer data or secondary data by usingthe qualitative approach that emphasized to descriptive analyzesbased on sociology jurisdiction research, Tho result of the researchpressed the implementation of land consolidation of towns fo houses inthe district of sidoardjo, lt is in the regulation of the Head of rhe randnational institution no 4 at 1991 according to the concept of the pran ofthe location sysfem of area (RTRW) the district of Sidoardjo, Theimplementation of this land consolidation has been done with thesysfem of self-supporting people. The problems come in the program ofthe land consolidation to stay can be handled by the people,Keywords : land consolidation, urban, residence